2011
DOI: 10.1097/ijg.0b013e3181e08137
|View full text |Cite
|
Sign up to set email alerts
|

Perimetric Progression in Open Angle Glaucoma and the Visual Field Index (VFI)

Abstract: The mean VFI regression slope in our cohort of eyes without perimetric progression showed a statistically significant difference compared with those with suspected and definite progression. VFI analysis and GPA II both had similarly high specificity but low sensitivity when compared with expert consensus opinion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Several authors have studied the sensitivity and specificity of GPA II event analysis, with contradictory results. Ang et al, 13 using the opinion of four experts as their reference standard, found rates of sensitivity and specificity (41% and 90%, respectively) that were very similar to our values. However other authors 1,14 have obtained higher rates of sensitivity for GPA II when the reference standard comprised experts using objective systems to detect progression such as those of Hodapp et al 15 or Boden et al 16 based on pattern deviation plot.…”
Section: Discussionsupporting
confidence: 91%
“…Several authors have studied the sensitivity and specificity of GPA II event analysis, with contradictory results. Ang et al, 13 using the opinion of four experts as their reference standard, found rates of sensitivity and specificity (41% and 90%, respectively) that were very similar to our values. However other authors 1,14 have obtained higher rates of sensitivity for GPA II when the reference standard comprised experts using objective systems to detect progression such as those of Hodapp et al 15 or Boden et al 16 based on pattern deviation plot.…”
Section: Discussionsupporting
confidence: 91%
“…1 VFI was meant to address some of the limitations of MD and PSD; and since its introduction, VFI has been used extensively to quantify the amount of VF loss in clinical studies. [3][4][5][6][7][8][9][10][11][12][13] The results of our study show that a significantly steep step in the VFI scale can occur when MD crosses the À20 dB mark and the VFI estimation strategy changes from PDPP to TDPP.…”
Section: Discussionmentioning
confidence: 62%
“…Since its introduction, numerous studies have used VFI to quantify the amount of visual function remaining in an eye. [3][4][5][6][7][8][9][10][11][12][13] However, little is known about the behavior of VFI when the estimation of VFI changes from PDPP to TDPP as the MD crosses the À20 dB threshold. Bengtsson and Heijl in their original article on VFI mentioned that ''shifting from pattern deviation probabilities to total deviation probabilities for identification of depressed points is likely to result in a slight stepwise worsening of VFI near MD values of À20 dB.''…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies evaluating trend-based analyses have ignored the magnitude of the slope and only considered the P-value associated with it. 11,[24][25][26] Our approach appears to be less sensitive (and more specific) than other studies. Employing a criterion that did not consider the magnitude of the slope could have increased the sensitivity (at the cost of specificity) of the analysis to detect progression.…”
Section: Discussionmentioning
confidence: 75%